Aesthetics of acting performance in contemporary directive trends (image theater as a model) (Journal of the College of Basic Education, 2022)
Art has not been, throughout the ages, separate from the intellectual, philosophical, or social structures that characterize society. On the contrary, there was a dialectical relationship that developed with the development of human society and the reproduction of its ideas, and according to ideological aesthetic affiliations, the artist’s view changed from one era to another. Doctrines and trends were formed that were unique in their view and vision of beauty according to their intellectual affiliation and the type of stage that characterizes them. Theatrical trends were not far from these affiliations, especially the acting performance. To a scenic reality, present in front of the viewer. And the performance of the actor is manifested through the act that achieves access to the discovery of aesthetic, cognitive and emotional values by making the feelings felt for the spectator and ascending with feelings to the feelings. According to this conception, the work of art is liberated